Pemodelan Tutupan Lahan Untuk Menjamin Keberlanjutan Debit Sungai (Suatu Studi Di Sub DAS Cikapundung-Maribaya) - Aditya Dwifebri Christian Wibowo; Mahawan Karuniasa; Dwita Sutjiningsih (Universitas Negeri Jakarta, 2021)
Changes in land use in the Cikapundung watershed, ie changes in forest land to built-up land, have an impact on the quantity of river water. Changes in land use in the Cikapundung River catchment are not ideal conditions for absorbing water. If land conversion is not controlled, it can have a large impact on reducing the availability of water resources for subordinate areas or what is called water scarcity. Analysis that takes into account land use and discharge can be done with several hydrological analysis methods, one of them is the Soil Conservation Service Curve Number (SCS-CN) method. Based on the calculation, the CN value was changed in 2014 from 57.275 to 62.591 where land cover changes began to occur. Keywords: land use, river water, water scarcity, hydrology, CN value